Association between depression and HIV infection vulnerable populations in United States adults: a cross-sectional analysis of NHANES from 1999 to 2018 - Xu, Yan; Huang, Yuexin; Peng, Jie; Tang, Ruiti; Luo, Bin; Xia, Zhiwei (Frontiers in Public Health, 2023)
Background: Although the government has made a commitment to advance education on HIV disclosure, depression continues to play a significant role in whether people living with HIV (PLWH) choose to disclose their HIV status to families or friends. Vulnerable populations who are at risk of contracting HIV may also be more susceptible to mental illness. However, there is a limited understanding of the association between depression and vulnerable populations affects by HIV among US adults. We aimed to explore the incidence of depression in the HIV infection vulnerable populations and assessed the association between the HIV infection vulnerable populations and depression. Methods: We analyzed the most current statistics from the National Health and Nutrition Examination Survey (NHANES), that included 16584 participants aged 18 years or older between 1999 to 2018. PHQ-9 was used to evaluate symptoms of depressive disorder. Demographic characteristics were compared between the HIV infection vulnerable groups and HIV infection low-risk groups. Multivariable logistic regression analysis was also carried out to evaluate the odds rate and association between the HIV infection vulnerable populations and depression. Results: Based on the most recent statistics from NHANES, HIV infection vulnerable populations were male, younger, less married or living together, non-Hispanic White people, lower income, and lower body mass index (BMI), with higher levels of cigarette smoking, alcohol drinking, a higher prevalence of depression, lower prevalence of hypertension and diabetes mellitus (DM) (p < 0.05). Additionally, individuals with severe depression had a higher prevalence of cardiovascular disease (CVD), hypertension, DM, chronic kidney disease (CKD), and a higher proportion of HIV infection vulnerable populations and less married or living together (p < 0.01). Finally, the odds of depression from the logistic regression were significantly increased in HIV infection vulnerable groups (p < 0.01) Conclusion: Depression might be associated with HIV infection vulnerable populations in the US adults. More research is needed to evaluate the association between HIV infection vulnerable populations and depression and explore their causal associations. In addition, prevention efforts focusing on HIV disclosure and HIV infection vulnerable populations in the US should address common co-prevalent depression to reduce new HIV infections.